(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
Nationalism can be addressed as one of the main forces in modern world. Explaining the mechanisms behind its functioning had been one of the tasks of Ernest Gellner’s works. Throughout the comparison of the thesis exposed in three books: Thought and Change written in 1964, Nations and Nationalism written in 1983, and Nationalism, edited posthumous in 1997, the paper tries to reconstruct the argumentations adopted by the author to face the problem of the variety of the different species of nationalism. At the beginning of his career, Gellner elaborates a “dynamic” theory of nationalism where the main differences between its manifestations are the effect of the uneven impact of the tidal wave of industrialization that invests different territories in different times. Twenty years later, event thought the author maintains the theory of the uneven impact of the tidal wave, he tries to elaborate a typology of nationalism, that can be seen as a “static” theory valid independently from historical and geographical circumstances. But in the posthumous book Gellner abandons the typology and develops a deeper dynamic theory for explaining the nationalism in Europe. Starting from the variety and phases of the phenomenon the paper tries to presents the different ways how Gellner imagined the future of nationalism: the author elaborate, on the basis of David Hume’s theory of religion, the idea that we will assist at an ebb and flow: from the agriculture era, where culture and State do not coincide, the industrialization glorified the connection between culture/language and State, but the mature industrial society will contemplate a new balance where culture and State won’t coincide anymore.